PENGARUH KUALITAS PRODUK, CITRA MEREK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN - Muhammad Gilang Yulianzha; Sinthon L Siahaan (LPPM Universitas Asa Indonesia, 2025)
This study aims to analyze the influence of product quality, brand image, and promotion on purchasing decisions for Kahf facial wash. This study used a quantitative method, distributing questionnaires to 100 respondents who use Kahf facial wash products. Data were obtained using IBM SPPS Statistics version 25 to determine the relationship between the variables in the research method. The analysis results indicate that product quality, brand image, and promotion have a positive influence on purchasing decisions for Kahf facial wash products.